Analysis and Output Power Control of Unidirectional Secondary-Resonant Single-Active-Half-Bridge DC-DC Converter - Cao Anh Tuan (MDPI AG, 2021)
Development of high-frequency-isolated DC-DC converters is underway for charging and discharging electric vehicle batteries. As a charger, a Single Active Bridge (SAB) converter, which is composed of a primary full-bridge converter, a high-frequency transformer, and a secondary full-bridge diode rectifier circuit, has been proposed as a unidirectional high frequency isolated DC-DC converter. In this paper, as a simple circuit configuration, a Secondary-Resonant Single-Active-Half-Bridge (SR-SAHB) converter, in which the primary and secondary circuits of the SAB converter are both half-bridge circuits, and a resonant capacitor connected in parallel to each secondary diode, is created. Due to the partial resonance on the secondary side, power transmission with unity transformer turn ratio and unity voltage conversion ratio can be realized, and a high total input power factor of the transformer can be achieved. As a result, the maximum voltage and current of the switching devices and the transformer voltage can be reduced. Moreover, soft switching in all commutations can be realized. The operation waveform is analyzed, and output power control is derived using the variable frequency control method. The effectiveness of the proposed SR-SAHB has been verified by experimental results using a 2.4 kW 20 kHz, 265 V laboratory prototype.